Comparative kinematic analysis of high-speed treadmill vs. overground sprinting across athletic levels and sex - Montalvo, S; Gonzales, F; Gruber, L; Gonzalez, M; Dietze-Hermosa, M; Dorgo, S. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: This investigation aimed to dissect the kinematic differences in sprinting between high-speed treadmill and overground conditions, examining how these variations are influenced by the athlete`s training status and biological sex.